MENGELOLA TEAMWORK DAN EMOTIONAL INTELLIGENCE SUMBER DAYA MANUSIA TENAGA KEPENDIDIKAN DI KOTA SERANG - Ranthy Pancasasti (Tirtayasa Ekonomika, 2019)
The purpose of this study was to analyze the magnitude of the influence: (1) transformational leadership on teamwork, (2) organizational climate on teamwork, (3) emotional intelligence on teamwork. The data obtained in this study were analyzed using quantitative and qualitative analysis methods. The population in this study were Human Resources for elementary school (SD) education staff in Serang City totaling 433 people. Sampling is done by random sampling method of 100 respondents. Primary data in this study comes directly from respondents. Secondary data was sourced from the Education Office and the Serang City and Banten Province Statistic Center, books, internet, and other parties related to this research. Data collection techniques were carried out by interviews, questionnaires, and documentation studies. The data obtained in this study were analyzed using quantitative and qualitative analysis methods (tabulation analysis methods, descriptive, focus group discussion (FGD), and root case analysis (RCA)). In accordance with the results of this study that Transformational Leadership (X1) has a direct effect on Teamwork (Y), Organizational Climate (X2) has a positive direct effect on Teamwork (Y), Emotional Intelliegence (X3) has a positive direct effect on Teamwork (Y)